2017
DOI: 10.1186/s12882-017-0741-0
|View full text |Cite
|
Sign up to set email alerts
|

Dissolved molecular hydrogen (H2) in Peritoneal Dialysis (PD) solutions preserves mesothelial cells and peritoneal membrane integrity

Abstract: BackgroundPeritoneal dialysis (PD) is used as renal replacement therapy in patients with end-stage kidney disease. However, peritoneal membrane failure remains problematic and constitutes a critical cause of PD discontinuation. Recent studies have revealed the unique biological action of molecular hydrogen (H2) as an anti-oxidant, which ameliorates tissue injury. In the present study, we aimed to examine the effects of H2 on the peritoneal membrane of experimental PD rats.MethodEight-week-old male Sprague-Dawl… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
12
0
1

Year Published

2019
2019
2023
2023

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 15 publications
(18 citation statements)
references
References 28 publications
(29 reference statements)
1
12
0
1
Order By: Relevance
“…39,40 The hydrogen-containing peritoneal dialysate was first applied in rat model, and peritoneal fibrosis is effectively prevented after the administration of peritoneal dialysis. 20 There was a case report in which hydrogen-containing peritoneal dialysate and hemodialysis solution were applied for 63 days in an encapsulated peritoneal sclerosis (EPS) patient, and the peritoneal biopsy result showed that the intestinal cysts were not obvious. 21 The development of hydrogen-containing peritoneal dialysate is undoubtedly promising because of its safety and the antioxidant properties.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…39,40 The hydrogen-containing peritoneal dialysate was first applied in rat model, and peritoneal fibrosis is effectively prevented after the administration of peritoneal dialysis. 20 There was a case report in which hydrogen-containing peritoneal dialysate and hemodialysis solution were applied for 63 days in an encapsulated peritoneal sclerosis (EPS) patient, and the peritoneal biopsy result showed that the intestinal cysts were not obvious. 21 The development of hydrogen-containing peritoneal dialysate is undoubtedly promising because of its safety and the antioxidant properties.…”
Section: Discussionmentioning
confidence: 99%
“…Hydrogen has already been reported to protect kidney, liver, heart, and lung from fibrosis . Studies have also suggested that peritoneal dialysate containing hydrogen could preserve MCs, indicating hydrogen may suppress peritoneal fibrosis . A clinical case report has indicated that hydrogen‐dissolved peritoneal dialysate could successfully treat a patient with encapsulating peritoneal sclerosis .…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…It has become a major alternative treatment for patients with end-stage renal disease worldwide [1]. However, persistent exposure of peritoneum to bio-incompatible peritoneal dialysis fluid (PDF) leads to peritoneal fibrosis, which decreases ultrafiltration capacity of peritoneum and limits its clinic application [2,3]. To date, there is no available treatment to prevent peritoneal fibrosis or halt its progression.…”
Section: Introductionmentioning
confidence: 99%
“…H 2 exerts anti-oxidative and anti-inflammatory effects [152]. In a less aggressive model of peritoneal damage than chlorhexidine administration, i.e., single injection of a neutral pH PD solution with low GDP content over 10 days in rats, the addition of H 2 mitigated submesothelial cell infiltration, mesothelial cell proliferation and apoptosis, and vimentin positivity, with the latter suggesting less MMT, but this could not be reconfirmed by other MMT markers [153]. Following an unsuccessful attempt to treat full-blown, histologically proven EPS with prednisolone for 30 days, Terawaki et al added dissolved H 2 to the hemodialysate, and 10 days later, also to the peritoneal lavage fluid.…”
Section: Experimental Approaches To Eps Treatmentmentioning
confidence: 99%